Desenvolvimento e caracterização de organogéis com diferentes óleos e ceras vegetais - Amaral, Júlia Ketchkech (Universidade Federal de São Carlos, 2025)
Consumers are increasingly concerned about eating healthier foods. As a result, health authorities have encouraged the development of strategies aimed at creating healthier alternatives, including the elimination of trans fats and the reduction of saturated fatty acids. In this context, organogel technology has emerged as an alternative, offering benefits beyond nutritional aspects, such as being a simpler and more cost-effective process. The objective of this project was to develop organogels using different vegetable oils, based on their degree of saturation, and to evaluate the combination of two vegetable waxes (candelilla and beeswax) in different proportions. A total of twenty-one organogels were formulated with varying ratios of beeswax to candelilla wax (0:6, 1:5, 2:4, 3:3, 4:2, 5:1, and 6:0 % (w/w)) using soybean, canola, and sunflower oils. The organogels were evaluated for texture, adhesiveness, rheological properties, thermal stability, and oil-binding capacity. The results showed that the addition of candelilla wax increased the firmness and stability of the organogels, especially when combined with beeswax. The organogels exhibited high oil-binding capacity and variable stability depending on the combination of vegetable oil and wax used, with the best stability observed in gels made with sunflower oil and a mixture of beeswax and candelilla wax. Oils with a high content of unsaturated fatty acids, such as sunflower oil, showed better performance in terms of mechanical resistance, firmness, and stability. Rheological analyses showed that the Herschel-Bulkley model fit the data well, indicating that the organogels exhibited pseudoplastic behavior with yield stress. Among the formulations tested, those with a 4:2 ratio of beeswax to candelilla wax showed the highest stability and, therefore, greater potential for food applications. Thus, the results confirm that organogels are viable alternatives to conventional fats and have potential for industrial application.
Development and characterization of organogels with different vegetable oils and waxes
Keywords: Oleogéis; Cera de candelilla; Cera de abelha; Propriedades reológicas; Oleogels; Candelilla wax; Beeswax; Rheological properties; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS; 3. Saúde e Bem-Estar